Quantitative assessment of automated purification and concentration of E. coli bacteria - Nina Sara Fraticelli Guzmán; Mohamed W. Badawy; Max A. Stockslager; Michael L. Farrell; Caitlin van Zyl; Seth Stewart; David L. Hu; Craig R. Forest (SLAS Technology, 2023)
Automated methods for rapidly purifying and concentrating bacteria from environmental interferents are needed in next-generation applications for anything from water purification to biological weapons detection. Though previous work has been performed by other researchers in this area, there is still a need to create an automated system that can both purify and concentrate target pathogens in a timely manner with readily available and replaceable components that could be easily integrated with a detection mechanism. Thus, the objective of this work was to design, build, and demonstrate the effectiveness of an automated system, the Automated Dual-filter method for Applied Recovery, or aDARE. aDARE uses a custom LABVIEW program that guides the flow of bacterial samples through a pair of size-based separation membranes to capture and elute the target bacteria. Using aDARE, we eliminated 95% of the interfering beads of a 5 mL-sample volume containing 107 CFU/mL of E. coli contaminated with 2 µm and 10 µm polystyrene beads at 106 beads/mL concentration., The target bacteria were concentrated to more than twice the initial concentration in 900 µL of eluent, resulting in an enrichment ratio for the target bacteria of 42 ± 13 in 5.5 min. These results show the feasibility and effectiveness of using size-based filtration membranes to purify and concentrate a target bacterium, in this case E. coli, in an automated system.